Photocatalytic Degradation of Oseltamivir Phosphate and Residual Toxicity Evaluation of its Metabolites as a Sustainable Solution for Antiviral Drug Pollution - Abd El-Nasser H. M. Muhanny; Hanem M. Awad; Nourhan Hassan; Mona S. Ragab; Ola R. Shehab (Water, Air, & Soil Pollution, 2026)
The global consumption of antiviral drugs (AVD) during the ongoing pandemic has overwhelmed wastewater treatment plants, which struggle to effectively remove these compounds due to their hydrophilic nature. Current methods fall short of fully degrading AVDs, leaving behind potentially harmful residues. In this study, we aim to investigate the photocatalytic degradation of oseltamivir phosphate under UV light, with and without the presence of catalysts. To address this challenge, we explored the use of titanium dioxide (TiO 2 ) as a cost-effective and highly stable photocatalyst. In combination with carbon nanotubes and UV-A radiation (365 nm), TiO 2 demonstrated exceptional efficiency in degrading oseltamivir phosphate, a common antiviral drug. Under optimized conditions, initial concentration (C0) of 1 mg/L, TiO 2 and carbon nanotube catalyst concentration (Ccat) of 0.1 g/L, and pH of 6.0, the system achieved complete degradation (100%). The degradation process followed pseudo-first-order kinetics with a strong correlation coefficient (r 2 = 0.8593). To confirm the degradation, we monitored changes in pH, Raman shifts, and FTIR spectra before and after treatment. Analytical methods, including UV–visible spectrophotometry and High-Performance Liquid Chromatography (HPLC), were used to quantify the degradation efficiency. Moreover, toxicity studies on wheat seeds indicated that the metabolites produced during oseltamivir phosphate degradation were non-toxic, suggesting the process is environmentally safe. This approach offers a promising solution for addressing AVD pollution in wastewater while minimizing ecological risks.

Addressing global food challenges with microalgae: Green yogurt enriched with Spirulina platensis as a sustainable probiotic dairy product for improved health and nutrition - Nasser S. Flefil; Hanem Awad; Ahmed M. Abd El-Sabour; Asmaa Negm El-Dein (Food and Humanity, 2025)

Phytochemical analysis and determination of antioxidant, anti-cholesterol, anti-inflammatory and anti-proliferative activities of Gerbera jamesonii flowers - Shaimaa Negm El-Dein; Amal Hussein; Marwa S. Abu-Bakr; Asmaa Negm El-Dein; Hanem M. Awad; Ehab A. Ragab (Advances in Traditional Medicine, 2023)

Solar photo-oxidation of recalcitrant industrial wastewater: a review - Ahmed Tawfik; Mohamed Gar Alalm; Hanem M. Awad; Muhammad Islam; Muhammad Abdul Qyyum; Ala’a H. Al-Muhtaseb; Ahmed I. Osman; Moonyong Lee (Environmental Chemistry Letters, 2022)
Conventional methods to clean wastewater actually lead to incomplete treatments, calling for advanced technologies to degrade recalcitrant pollutants. Herein we review solar photo-oxidation to degrade the recalcitrant contaminants in industrial wastewater, with focus on photocatalysts, reactor design and the photo-Fenton process. We discuss limitations due to low visible-light absorption, catalyst collection and reusability, and production of toxic by-products. Photodegradation of refractory organics by solar light is controlled by pH, photocatalyst composition and bandgap, pollutant properties and concentration, irradiation type and intensity, catalyst loading, and the water matrix.

Harvesting zero waste from co-digested fruit and vegetable peels via integrated fermentation and pyrolysis processes - Mohamed Soltan; Mohamed Elsamadony; Alsayed Mostafa; Hanem Awad; Ahmed Tawfik (Environmental Science and Pollution Research, 2019)

Flavones from Heavenly Blue as modulators of Alzheimer’s amyloid-beta peptide (Aβ) production - Hanem M. Awad; Howaida I. Abd-Alla; Mohamed A. Ibrahim; Eslam R. El-Sawy; Mohamed M. Abdalla (Medicinal Chemistry Research, 2018)

Synthesis and in vitro antitumor evaluation of novel Schiff bases - Ashraf S. Hassan; Hanem M. Awad; Asmaa A. Magd-El-Din; Taghrid S. Hafez (Medicinal Chemistry Research, 2018)

Anticancer activity of some [1,2,4]triazepino[2,3-a] quinazoline derivatives: monolayer and multicellular spheroids in vitro models - Hanem M. Awad; Walid Fayad; Salwa M. El-Hallouty; Thoraya A. Farghaly; Mohamad M. Abdallah (Medicinal Chemistry Research, 2016)

In vitro anti-nitrosative, antioxidant, and cytotoxicity activities of plant flavonoids: a comparative study - Hanem M. Awad; Howaida I. Abd-Alla; Khaled H. Mahmoud; Sayed A. El-Toumy (Medicinal Chemistry Research, 2014)